Integrasi Sistem Informasi Geografis Pada Sistem Pengaduan Masyarakat Berbasis Web - Ajitama, Rahmadani; Widyaningsih, Pipin; Nurmalitasari (Fakultas Teknik Universitas Hamzanwadi, 2025)
Ngabenrejo Village, located in Grobogan Subdistrict, Grobogan Regency, Central Java Province, faces various public issues such as damaged roads, garbage accumulation, flooding, and more. The management of public complaints is still conducted manually, where residents must submit written reports to the village officials. This method often results in unrecorded complaints, difficulty in follow-up, and the risk of reports being overlooked due to the absence of a structured monitoring system. This research aims to design and develop a web-based public complaint system integrated with a Geographic Information System (GIS), referred to in Indonesian as Sistem Informasi Geografis (SIG). The system development method used is prototyping, supported by observation, interviews, and literature studies. The outcome of this research is a web-based complaint system that allows residents to submit complaints online along with the geographical location of the reported issue. Key features include complaint location mapping, email notifications to the complainants, and a dashboard for village officials to manage reports. This system is expected to improve the efficiency of public services and enhance transparency in handling community complaints, as each report is properly recorded, easily monitored, and can be systematically followed up.